2022
DOI: 10.1002/cpt.2681
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of Efficacy from Adults to Pediatric Patients of Drugs for Treatment of Partial Onset Seizures: A Regulatory Perspective

Abstract: Study HighlightsWHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? Based on nonclinical and clinical evidence, the pathophysiology of partial onset seizures (POS) is similar in pediatric patients ≥ 1 month of age and adults. WHAT QUESTION DID THIS STUDY ADDRESS?  This analysis addresses whether drugs indicated for the treatment of POS in adults and pediatric patients exhibit similar exposure-response relationships for efficacy. Such information can provide support for extrapolation of efficacy from adult to pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…As the sparse pregabalin concentrations and the population PK modeling confirmed pregabalin exposure, the lack of statistical difference at the lower dose in PERIWINKLE could be due to a larger placebo response, hence the smaller placebo‐adjusted efficacy vs. adult studies 2 . After taking into account the different placebo responses in the joint analysis, pregabalin demonstrated a similar E‐R relationship in adult and pediatric (4–16 years) patients with FOS, consistent with the analysis that supported the full efficacy extrapolation from adults with FOS to this age group 29 . Considering the FDA’s advice notice and the totality of the pregabalin data, pregabalin dosage recommendations in the prescription label 2,3 were based on full efficacy extrapolation by matching pregabalin exposures at the approved adult doses, and the safety and tolerability observed in the pregabalin pediatric studies.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As the sparse pregabalin concentrations and the population PK modeling confirmed pregabalin exposure, the lack of statistical difference at the lower dose in PERIWINKLE could be due to a larger placebo response, hence the smaller placebo‐adjusted efficacy vs. adult studies 2 . After taking into account the different placebo responses in the joint analysis, pregabalin demonstrated a similar E‐R relationship in adult and pediatric (4–16 years) patients with FOS, consistent with the analysis that supported the full efficacy extrapolation from adults with FOS to this age group 29 . Considering the FDA’s advice notice and the totality of the pregabalin data, pregabalin dosage recommendations in the prescription label 2,3 were based on full efficacy extrapolation by matching pregabalin exposures at the approved adult doses, and the safety and tolerability observed in the pregabalin pediatric studies.…”
Section: Discussionsupporting
confidence: 79%
“…More specifically, Rheims et al ., in 2011, demonstrated that responder rates were significantly higher in more recent studies than in older studies 30 . For pediatric patients 4–16 years, anatomic and clinical features of FOS are similar to adults, as are responses to AEDs 31–33 and E‐R relationships 29 . Our analyses utilizing pregabalin data are consistent with these conclusions, and provide further validation of E‐R relationship similarity in adult and pediatric FOS populations.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…More recently, the U.S. FDA concluded the efficacy of drugs approved for FOS can be extrapolated to pediatric patients 1 month of age and older based on an analysis by Mehrotra et al where they conducted an exposure-response relationship analysis of 8 drugs (levetiracetam, oxcarbazepine, topiramate, lamotrigine, gabapentin, perampanel, tiagabine, and vigabatrin) approved for FOS in adults and pediatric patients. 12 Several examples of extrapolation of efficacy using popPK modeling of ASMs to the pediatric population exist in the literature (Table 2). Schoemaker et al used model-informed meta-analysis where they used an existing PK/PD model for brivaracetam, and this was applied to an adult-pediatric dataset of levetiracetam since these two drugs belong to the same drug class.…”
Section: Role Of Extrapolation Of Efficacy In Epilepsy and Seizure Tr...mentioning
confidence: 99%
“…In the literature, the extrapolation of efficacy for ASMs via exposure‐response (i.e., seizure frequency reduction) analysis is made possible through modeling and simulation techniques such as population pharmacokinetic (popPK) modeling or model‐informed meta‐analysis 10–14 . To support the extrapolation of efficacy, clinical data from an adequately designed PK study in the pediatric population is still needed 8 .…”
Section: Introductionmentioning
confidence: 99%